Surface Refractive Surgery Outcomes in Israeli Combat Pilots - Asaf Achiron; Nadav Shemesh; Tal Yahalomi; Dana Barequet; Amit Biran; Eliya Levinger; Nadav Levinger; Shmuel Levinger; Ami Hirsch (BioMedInformatics, 2022)
Photorefractive keratectomy (PRK) has long been the method of choice for refractive surgery in pilots, and was FDA approved for U.S. Air Force aviators in 2000. We retrospectively reviewed the medical records of 16 male combat pilots (mean age 25.0 ± 5.5 years) who had undergone bilateral laser refractive surgery with surface ablation (alcohol-assisted PRK: 81.25%, transepithelial-PRK: 18.75%), and who had a mean baseline spherical equivalent (SE) of −2.1 ± 0.7 D in the right eye, and −2.0 ± 0.7 D in the left. The mean follow-up was 8.4 ± 6.6 months. On the last visit, the uncorrected visual acuity (UCVA) had improved from 0.75 ± 0.33 logMar to −0.02 ± 0.03 logMar (p < 0.001), and from 0.72 ± 0.36 logMar to −0.02 ± 0.05 logMar (p < 0.001), for the right and left eyes, respectively. The percentages of participants with a right eye UCVA of at least 0.0, −0.08, and −0.18 logMAR (6/6, 6/5, and 6/4 Snellen in meters) were 100%, 37.5%, and 6.2%, respectively, and for the left eye, 93.7%, 43.75%, and 6.2%, respectively. No complications occurred. This is the first study to assess refractive surgery outcomes in a cohort of Israeli combat pilots. Surface refractive surgery effectively improved UCVA and reduced spectacle reliance for the members of this visually demanding profession.